FUNCIONALIDAD REPRODUCTIVA Y PERFIL NUTRICIONAL EN EL POSTPARTO DE VACAS TIPO LECHE EN LA REGIÓN AMAZÓNICA ECUATORIANA SUR (RAESUR) - Aguirre L.,; Quezada M.; Uchuari M.; Chavez R.; Barragan G. (Actas Iberoamericanas de Conservación Animal, 2015)
In the South Amazon Ecuadorian Region (RAEsur), the livestock is the main economic activity of the majority of families live this hot and humid environment, the dairy cattle in these area, are Bos taurus, those were brought from the upper parts of Andes, thereby they have a slow process of adaptation to this environment and the type of food, if this a join with poor technical management are factors that affect the animal's body condition and reproductive performance. In this investigation we evaluated the reproductive behavior and nutritional profile of 93 crossbred cows Holstein in the postpartum period, follow up period was 187 days. It was obtained: parturition-estrus interval of 88 days, in the population tested 25.4% not resumed its reproductive function in that period (pospartum anoestrus); the type of existing pasture grasses is in 87% of grasslands 􀀃Setaria sphacelata and 13% the Axonopus scoparius; cows with 􀀃most body condition (BC) at calving 􀀋􀂕􀀕􀀑􀀖􀀌􀀃 soon resumed the reproductive functionality versus those with less BC 􀀋􀂔2.2)􀀞 these animals are small with an average height of 1.23 m, where 70% of cows that resumed reproduction were of small stature; 􀀞􀀃the daily milk production in the period under review was 6.7 L/cow. The nutritional profile was made on serial blood samples at 45 days interval from calving to the resumption of estrus, 8 biochemical elements were analyzed: glucose, total protein, albumin, alkaline phosphatase, GOT, GPT, cholesterol, bilirubin, these results can be highlighted the high levels of enzymes alkaline phosphatase, GOT, GPT and bilirubin, far exceeding the normal values, also found that glucose level in cycling (45.0 mg/dl) and not cyclic cows (44.5 mg/dl) are lower compared to normal value (58.3 mg/dl), the other biochemical elements analyzed are within permitted ranges􀀞􀀃 thereby being able to diagnose these animals suffer liver damage which leads to having a short life and poor production, all it caused by the introduction to the area of Bos taurus animals that not have resistance or adaptation to the humid tropics.